2014
DOI: 10.1039/c4nr05301j
|View full text |Cite
|
Sign up to set email alerts
|

Study of Cytochrome c-DNA Interaction – Evaluation of Binding Sites on the Redox Protein

Abstract: Artificial assemblies consisting of the cationic cytochrome c (cyt c) and double-stranded DNA are interesting for the field of biohybrid systems because of the high electro-activity of the incorporated redox protein. However, little is known about the interactions between these two biomolecules. Here, the complex of reduced cyt c and a 41 base pair oligonucleotide was characterized in solution as a function of pH and ionic strength. Persistent cyt c-DNA agglomerates were observed by UV-vis and DLS (dynamic lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…It has to be emphasized here that DNA acts only as a structural support to bind a large amount of cyt c. 40 This is based on a rather strong interaction in acidic solutions which is mainly of electrostatic nature and has been elucidated previously. 41 The DNA molecule has no redox activity in the potential range tested here.…”
Section: ■ Results and Discussionmentioning
confidence: 81%
“…It has to be emphasized here that DNA acts only as a structural support to bind a large amount of cyt c. 40 This is based on a rather strong interaction in acidic solutions which is mainly of electrostatic nature and has been elucidated previously. 41 The DNA molecule has no redox activity in the potential range tested here.…”
Section: ■ Results and Discussionmentioning
confidence: 81%
“…However, the extent of interaction may depend upon different microenvironment. 32 For the complex monolayer at the interface, DNA has been used as the building block for the Cyt c/l-DNA complex molecular network. In our work, pH of the subphase aer spreading Cyt c/l-DNA mixed solution was 6.2.…”
Section: Resultsmentioning
confidence: 99%
“…30,31 Research suggests that Cyt c/DNA multilayered systems exhibit highest accumulations of redox active materials. 32 However, for specic device or applications, it is very crucial to tailor the properties by changing the orientation of DNA/protein complex assemblies onto solid substrate. LB technique, in this regard, is an elegant choice because of its ability to manipulate molecular orientation and prepare ultrathin lms with highest materials transfer ratio.…”
Section: Introductionmentioning
confidence: 99%
“…In several studies on combination between DNA-cyt c it has been demonstrated that electron exchange between cyt c-cyt c can be realized. 295,296 An intensive study by Stieger et Here, combination with the third biomolecule, DNA, has been employed and stable photoactive multilayers (PSI-cyt c-DNA) n have been achieved. 85 c) integration of PSI-cyt c inside a 3D electrode architecture.…”
Section: Electrical Communication With Biomoleculesmentioning
confidence: 99%